Characteristics and Clinical Assessment of Elbow Pain in Youth Baseball Players - Hironobu Koseki; Shiro Kajiyama; Takayuki Shida; Iku Tomonaga; Yuta Nishiyama; Daisuke Yoshida; Satoshi Mizukami; Kazuhiro Yamaguchi; Chieko Imai (MDPI AG, 2024)
Elbow injuries related to the throwing motion in baseball during the growth period present difficulties for early detection and may cause serious future disabilities. This study aimed to comprehensively determine the characteristics and clinical assessment of elbow pain in youth baseball players. Two hundred and sixteen young baseball players underwent elbow medical examination. Basic information and physical examination, clinical assessment, and ultrasonography results were examined. Univariate analyses were statistically performed between the pain-free (98 participants) and elbow pain (118 participants) groups. The mean age was 11.6 years, and ultrasonographic abnormalities were found on the medial side of the elbow in 37.5%. In total, 118 (54.6%) participants experienced elbow pain, with 64.4% of them complaining of elbow pain on the medial side. Players with multiple positions (≥2 positions) had a significantly higher prevalence of elbow pain. Height, weight, length of baseball experience, and positive rates of horizontal flexion and moving valgus stress tests were higher in the elbow pain group than in the pain-free group. The risk factors and clinical assessment for elbow pain are useful for the prevention and early detection of throwing elbow injuries in youth baseball players.